PENGARUH PENGGUNAAN E-LKPD TERHADAP HASIL BELAJAR MATEMATIKA SEKOLAH DASAR - Yunni Arnidha; Norma Yunaini; Agata Alvi Dwi Tantri (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This study aimed to determine the effect of using the E-LKPD on elementary school mathematics learning outcomes. This research is motivated by technological developments and the low utilization of E-LKPD in mathematics learning. The research method used is the quantitative method